Patrón esquelético y su asociación con los tipos de maloclusión de angle en los alumnos de la E.A.P. de Odontología de la Universidad Nacional Hermilio Valdizán abril - agosto 2013 - Cardenas Criales, Jesus (2017)
In literature it has not found a specific piece of information on the relations that can show up between the skeletal boss and the types of malocclusion. In general the correlation that exists between skeletal classes and types of malocclusion according to Angle is considered like a fact, what a bad diagnosis can result in and therefore to come true an unsuitable and unstable treatment. The objective of this study was delving deeply into the knowledge on behalf of the odontologists of the E.A.P of Odontología of the UNHEVAL in the realization of a most complete and efficacious diagnosis, that in turn it proves to be more successful.